Soil Carbon and Microbial Processes in Agriculture Ecosystem - Chen, Yinglong; Saito, Masanori; Novotny, Etelvino Henrique (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As the global population and demand for food steadily increase, the maintenance and enhancement of soil productivity to ensure food security is becoming an important issue at the global level as global warming continues to progress. Soil carbon acts as a global carbon sink, playing a crucial role in soil fertility maintenance. Soil carbon is a complex product resulting from various microbial processes; it is a fragile entity, vulnerable to inappropriate human activity and global climate change. Soil microbes that utilize carbon efficiently may help to reduce carbon losses and increase carbon storage. This Special Issue highlights the current understanding of the dynamics of soil carbon and the microbial processes in agricultural ecosystems from the molecular level to the regional and global scales. The topics of interest in this Special Issue include carbon dynamics in plant-soil systems, the carbon balance, approaches to managing soil carbon maintenance and carbon sequestration, and related microbial processes in agricultural ecosystems.